Pengaruh Pendidikan Kesehatan terhadap Pengetahuan dan Sikap Siswa SMK dalam Menghadapi Bencana Banjir - Shari, Weni Widya; Ariyani, Hana; Zani, Andri Yan Prima (Jurnal Kesehatan, 2023)
Abstract Health education about flood disasters is urgently needed to increase students' knowledge and attitudes about flood disasters. The existence of this knowledge and attitude will help students to be prepared for disasters so that it will reduce the impact, losses and even fatalities that arise due to flood disasters. This study aims to explain the effect of health education on the level of knowledge and attitudes in dealing with floods in students of SMK Raflesia Depok. The research used the pre-experimental method, with pre- and post-test design in one group. The population in this study were students of SMK Raflesia Depok. The research sample was 32 people using a non-probability sampling technique, namely the consecutive sampling method. Data was collected through a questionnaire given before and after Health Education about flooding. The independent variable is health education while the dependent variable is knowledge and attitude. The statistical test used the Wilcoxon test with a significant α < 0.05 for the knowledge variable and a significant α < 0.10 for the attitude variable. The results showed that there was an increase in knowledge (p=0.000) and attitude (p=0.074) in Raflesia Depok Vocational High School students before and after Health Education. In addition, there is a relationship between knowledge and attitudes before education (p = 0.015) and after health education (p = 0.001), which means that the higher the knowledge, the better students' attitudes in facing floods. It can be concluded that there is an influence of Health Education in increasing the knowledge and attitudes in dealing with flood disasters in the Raflesia Depok Vocational High School students. It is hoped that schools will equip students with Health Education about flood disasters.